Mass atrocities, the responsibility to protect and the future of human rights : 'if not now, when?' - Adams, Simon, 1968- (United Kingdom: Taylor & Francis Group, 2021)
This book ambitiously weaves together history and politics to explain all of the major situations where mass atrocities have occurred, or been prevented, over the 15 years since the 'Responsibility to Protect' (R2P) was adopted at the 2005 UN World Summit--back cover.
Introduction: It wasn't supposed to be this way -- 1. Why humans commit atrocities and how societies can change -- 2. Regime change in Libya -- 3. Moments on the margins of Syria's civil war -- 4. Terrorism, genocide and the Islamic State -- 5. Climate change and mass atrocities -- 6. The fate of the Rohingya and the future of human rights -- 7. Conclusion: The mass graves that were not dug.
Includes bibliographical references (pages [134-135) and index.
Keywords: Responsibility to protect (International law); Atrocities -- Law and legislation; Human rights; Atrocities -- Law and legislation; Human rights; Responsibility to protect (International law)